2022
DOI: 10.1007/s13300-022-01267-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of iGlarLixi Versus Premix BIAsp 30 in Patients with Type 2 Diabetes Suboptimally Controlled by Basal Insulin in the UK

Abstract: Introduction iGlarLixi is indicated as an adjunct to diet and exercise in addition to metformin (with or without sodium-glucose cotransporter-2 inhibitors) to improve glycemic control in adults with insufficiently controlled type 2 diabetes (T2D). A cost-effectiveness analysis was conducted to compare iGlarLixi with premix biphasic insulin aspart 30 (BIAsp 30) in people with T2D suboptimally controlled with basal insulin (BI). Methods The IQVIA CORE Diabetes Model was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Similarly, a study in the UK showed that treatment acquisition was the main driver of cost differences between premix BIAsp 30 and iGlarLixi, making the latter a simple, cost-effective option for intensification [ 19 ]. Another study in the USA compared the healthcare resource utilization and costs for iGlarLixi with newly initiated free-dose combinations of basal insulin and GLP-1RA that were started either simultaneously or sequentially [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study in the UK showed that treatment acquisition was the main driver of cost differences between premix BIAsp 30 and iGlarLixi, making the latter a simple, cost-effective option for intensification [ 19 ]. Another study in the USA compared the healthcare resource utilization and costs for iGlarLixi with newly initiated free-dose combinations of basal insulin and GLP-1RA that were started either simultaneously or sequentially [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few economic evaluations of iGlarLixi in patients with T2DM to date. Recent cost-effectiveness study reports from the USA [ 18 ] and UK [ 19 ] revealed that iGlarLixi confers improved quality adjusted life years (QALYs) and lower costs compared to premix biphasic insulin aspart 30 (BIAsp) in people with suboptimal glycemic control on basal insulin. Additionally, total estimated costs were lowest for iGlarLixi compared with other fixed- and free-dose combinations of insulins plus GLP-1RA [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same cost-saving effect was also confirmed in an IGlarLixi add-on strategy in people with T2D treated with oral antihyperglycemic agents[ 60 ]. IGlarLixi showed slightly higher estimated QALYs at an acceptable higher cost with a reduction in the daily injection frequency compared with twice daily BIAsp 30[ 61 ]. The cost-effectiveness of these two FRCs appears to be different.…”
Section: Effects Of Frc Therapies On Patient-recorded Outcomesmentioning
confidence: 99%
“…(2) Promote metabolism. The premix feed is supplemented with vitamins and various microelements, which are essential active substances in the growth and metabolism of animals and active components of enzymes in the body [7], which are involved in the whole metabolic process of livestock and poultry growth, and thus the complete various life activities can be completed.…”
Section: Function Of Premix Feedmentioning
confidence: 99%